A feedback loop between Paxillin and Yorkie sustains Drosophila intestinal homeostasis and regeneration - Dan Jiang; Pengyue Li; Yi Lu; Jiaxin Tao; Xue Hao; Xiaodong Wang; Wei Wu; Jinjin Xu; Haoen Zhang; Xiaoyu Li; Yixing Chen; Yunyun Jin; et al. (Nature Communications, 2025)
Abstract Balanced self-renewal and differentiation of stem cells are crucial for maintaining tissue homeostasis, but the underlying mechanisms of this process remain poorly understood. Here, from an RNA interference (RNAi) screen in adult Drosophila intestinal stem cells (ISCs), we identify a factor, Pax, which is orthologous to mammalian PXN, coordinates the proliferation and differentiation of ISCs during both normal homeostasis and injury-induced midgut regeneration in Drosophila. Loss of Pax promotes ISC proliferation while suppressing its differentiation into absorptive enterocytes (ECs). Mechanistically, our findings demonstrate that Pax is a conserved target gene of the Hippo signaling pathway in both Drosophila and mammals. Subsequent investigations have revealed Pax interacts with Yki and enhances its cytoplasmic localization, thereby establishing a feedback regulatory mechanism that attenuates Yki activity and ultimately inhibits ISCs proliferation. Additionally, Pax induces the differentiation of ISCs into ECs by activating Notch expression, thus facilitating the differentiation process. Overall, our study highlights Pax as a pivotal component of the Hippo and Notch pathways in regulating midgut homeostasis, shedding light on this growth-related pathway in tissue maintenance and intestinal function.